2015
DOI: 10.3102/0002831215585562
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Collaboration in Instructional Teams and Student Achievement

Abstract: This study draws upon survey and administrative data on over 9,000 teachers in 336 Miami-Dade County public schools over 2 years to investigate the kinds of collaborations that exist in instructional teams across the district and whether these collaborations predict student achievement. While different kinds of teachers and schools report different collaboration quality, we find average collaboration quality is related to student achievement. Teachers and schools that engage in better quality collaboration hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
299
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(358 citation statements)
references
References 25 publications
12
299
0
17
Order By: Relevance
“…Since the 1970s the topic is being transferred to the schooling sector and educational research. In fact, most of the research in this field accredits collaboration to support many positive outcomes such as a better school quality (Goddard, Goddard, & TschannenMoran, 2007;Ronfeld, Matthew, Owens Farmer, McQueen, & Grissom, 2015), healthier teachers (Schaarschmidt, 2005) and -for this study the most important finding -a profound, positive impact on teacher professionalization (Avalos, 2011;Vangrieken, Dochy, Raes, & Kyndt, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Since the 1970s the topic is being transferred to the schooling sector and educational research. In fact, most of the research in this field accredits collaboration to support many positive outcomes such as a better school quality (Goddard, Goddard, & TschannenMoran, 2007;Ronfeld, Matthew, Owens Farmer, McQueen, & Grissom, 2015), healthier teachers (Schaarschmidt, 2005) and -for this study the most important finding -a profound, positive impact on teacher professionalization (Avalos, 2011;Vangrieken, Dochy, Raes, & Kyndt, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Most importantly, teacher collaboration has been positively linked to student achievement (Goddard, Goddard, & Tschannen-Moran, 2007;Kraft & Papay, 2014;Louis & Marks, 1998;Ronfeldt et al, 2015). Although hesitant to claim causality, researchers have suggested that the amount and quality of collaboration within a school corresponds with increased levels of student achievement (Goddard et al, 2007;Ronfeldt et al, 2015).…”
Section: Professional Development (Pd)mentioning
confidence: 99%
“…Teachers learned at faster rates working in schools where the quality of collaboration was higher (Ronfeldt, Farmer, McQueen, & Grissom, 2015), and they were found to be more eager, energized, and innovative toward teaching all students than those in lesser quality PLCs (McLaughlin & Talbert, 1993). Quality collaboration means dialogue in PLCs is regulated by group selected norms that focus primarily on student learning and provide teachers with feedback where trust and rapport are strong (Bolam, McMahon, Stoll, Thomas, & Wallace, 2005;Vescio et al 2008).…”
Section: Professional Development (Pd)mentioning
confidence: 99%
See 2 more Smart Citations